Changes in the physiological potential of sunn hemp seeds during storage - Bruna Neves Pereira da Silva; Tathiana Elisa Masetto; Luiz Carlos Ferreira de Souza (Pesquisa Agropecuária Tropical, 2022)
Sunn hemp (Crotalaria spectabilis)is widely used for soil correction and cover, but it is still necessary to know the characteristics that influence the storage of its seeds. This study aimed to evaluate the physiological quality of sunn hemp seeds under uncontrolled environmental conditions and in acclimatization chamber. A completely randomized experimental design was used, with four replicates, in subplots evaluated in different periods. Freshly harvested seeds and seeds at 90, 180 and 270 days of storage were evaluated for germination, first germination count, germination speed index, seedling emergence in the field, accelerated aging, cold test and seedling growth. The environment and storage time significantly influenced the seed germination and vigor. The seeds showed a high physiological performance for both the environmental conditions, maintaining the ability to produce normal seedlings up to approximately 150 days of storage, deteriorating afterwards, although without losing their germination capacity up to 270 days of storage.